Digital economy in Polish regions. Proposal of measurement via TOPSIS with generalized distance measure GDM - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2017)
Investing in digital infrastructure and building effective digital economy is currently considered as a basic condition for keeping international competitiveness of developed economies. In the case of developing countries in some economic models it is considered as a factor that can help to avoid middle income trap. From the regional perspective developing digital economy can support the process of convergence and closing development gap between the regions. As a result, a comparative research concerning the development level of digital economy is an important scientific task. In this context, the aim of the article is to assess and compare the development level of digital economy in Polish regions (NUTS 1). The digital economy is commonly considered as a multiple-criteria phenomenon. Thus, an approach based on TOPSIS method with application of generalized distance measure GDM was used in the analysis. Six diagnostic variables concerning digital infrastructure and level of its utilization were used. The research was conducted for the years 2012-2015 with application of Eurostat Data. The conducted analysis confirmed relatively quick progress in the field of building digital economy obtained by Polish regions.
Keywords: P25; C38; 330; digital economy; multiple-criteria analysis; TOPSIS; generalized distance measure GDM